Focus E-learning on Specific Small Target Groups (doi: 10.3991/ijac.v1i2.536) - Ratna, Vivek; Castelein, Folkert (International Journal of Advanced Corporate Learning (iJAC), 2008)
We hear criticism about the education system in several countries. Itâ??s been said that schools and many institutions are experimenting with several old methods of education that are not founded on scientific grounds but on (political) beliefs. Many organizations still deliver training in classrooms or push standard content via the internet to individual employees. In 2005 Bill Gates called secondary schools an outdated tool for the training of tomorrowâ??s workforce. This paper about e-learning and e-development will show trends in technology and in learning and cooperative behaviors. All these and other factors have an influence on effective learning. It deals with the importance of content-driven and small professionally coached online workgroups supporting a practical guided learning process through questions. This is a promising development that can take away many threats of the current education in schools and Organizations. Also, this approach shows under what conditions the concept of Life Long Learning can be successful. Organizations will have to pursue this if they wish to overcome â??the battle for the hard to find well educated employeeâ??. The conclusion is straight forward: formulate clear targets for formal and informal learning, know your audience, listen and create for them recognizable conditions and measure the ROI.